The Effect of Picture Series on Teaching English Writing - Halim, M. Labib Al; Arifin, Moh. (Pioneer: Journal of Language and Literature, 2022)
Junior high school students are expected to create short essays, and concise texts, according to the junior high school curriculum. The issue is that students are unable to communicate their thoughts. It is proved that when the teacher asks the students to write about recount text or narrative text, they only write a few sentences, and they also make mistakes in using grammar patterns. This research aims to reveal the effect of picture series in teaching writing, and whether students who were taught through a picture series goa t better scores than those who were taught through the conventional method. This research used a quasi-experimental design. The finding showed that picture series could enable students to explore their ideas. The students were able to create and use their imagination to write well after watching the picture series. The result of the T-test analysis showed that the sig (2-tailed) was 0.000, which was lower than 0.05 level significance (0.000 < 0.05). It was assumed that the mean score difference between the experimental and control groups was significant. Thus, it was enough to reject the null hypothesis, which means that picture series-based E-learning significantly affected students’ writing, especially in writing narrative text.